2009
DOI: 10.1002/jssc.200800590
|View full text |Cite
|
Sign up to set email alerts
|

Radial distribution of the contributions to band broadening of a silica‐based semi‐preparative monolithic column

Abstract: Using an on-column local electrochemical microdetector operated in the amperometric mode, band elution profiles were recorded at different radial locations at the exit of a 10 mm id, 100 mm long silica-based monolithic column. HETP plots were then acquired at each of these locations, and all these results were fitted to the Knox equation. This provided a spatial distribution of the values of the eddy diffusion (A), the molecular diffusion (B), and the resistance to the kinetics of mass transfer (C) terms. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This is a well-known problem, particularly for the rigid, but brittle, silica monoliths prepared with pure tetramethoxysilane . In analytical and semipreparative monolithic silica columns wall effects in general have been identified before to substantially affect the average cross-sectional plate height, and they are also known for capillary monoliths. , The lateral pore space heterogeneity and its large contribution to eddy dispersion is at present the main drawback of silica monoliths in chromatographic practice …”
Section: Resultsmentioning
confidence: 99%
“…This is a well-known problem, particularly for the rigid, but brittle, silica monoliths prepared with pure tetramethoxysilane . In analytical and semipreparative monolithic silica columns wall effects in general have been identified before to substantially affect the average cross-sectional plate height, and they are also known for capillary monoliths. , The lateral pore space heterogeneity and its large contribution to eddy dispersion is at present the main drawback of silica monoliths in chromatographic practice …”
Section: Resultsmentioning
confidence: 99%
“…However, the online version of record will be different from this version once it has been copyedited and typeset. Two notable examples where this idealized patchwork model could fall short are packed bed columns where the stacking of particles is disrupted near the side wall 13,14 , and sol-gel synthesized monolithic columns, where radial heterogeneities are present along the entire axis 15,16 . In the field of chromatography, these trans-column phenomena have been put forward as significant sources of axial dispersion in the columns being used [13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Long ago, many authors reported that HPLC columns are radially heterogeneous to a degree. It is probably impossible to prepare columns that are radially homogeneous. So, a strategy is needed that permits the derivation of reliable information on the actual characteristics of the radial heterogeneity of columns from the asymmetrical profiles of elution peaks.…”
mentioning
confidence: 99%